2017
DOI: 10.17129/botsci.636
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation in fruits and seeds of Ceiba aesculifolia and its relationship with germination and seedlings biomass

Abstract: Background: Morphologic variation in fruits and seeds affects the performance and adaptation of plants.Only a few studies have integrally analyzed these variables and their effects in plant germination and early growth in tropical dry forest (TDF). Questions: Do the size and shape of fruits influence the number and mass of seeds? Is there a positive relation between seed traits, germination and seedling growth? Species studied: Ceiba aesculifolia. Study site: A TDF growing in a lava field in Actopan, Veracruz:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…From these pods, 4.3, 8.3, and 87.4 wt% were determined for fibers, seeds, and husks, respectively. The results are in the range of those reported by Velázquez-Rosas et al (2017). The fibers were then collected and kept for further characterization.…”
Section: Fibers From Ceiba Aesculifoliasupporting
confidence: 76%
“…From these pods, 4.3, 8.3, and 87.4 wt% were determined for fibers, seeds, and husks, respectively. The results are in the range of those reported by Velázquez-Rosas et al (2017). The fibers were then collected and kept for further characterization.…”
Section: Fibers From Ceiba Aesculifoliasupporting
confidence: 76%
“…The research performed in several populations of C. aesculifolia throughout the Mexican SDFTs recognizes the species as a pioneer-secondary species, which can grow in shallow soils and higher hydric stress [28,29], as well as in low-soil P concentrations [30]. The seedlings have been shown to resist drought through high sapwood water storage capacity, and although this trait renders them vulnerable to xylem embolism, the buffering role of water storage allows the seedlings to maintain their water potential above the soil's potential as water stress intensifies [31].…”
Section: Ceiba Aesculifoliamentioning
confidence: 99%
“…Recent field work and greenhouse experiments by Velázquez-Rosas et al [28], Martínez-González et al [29] and Martínez-González et al [34] were centered on the importance of seed size variation during germination, during seedling establishment and seedling survival to foliar damage, respectively. Seed size seems to have an effect on germination of individuals emerging in pastures (disturbed areas), whereas there was no effect of seed size in conserved SDTF patches [29] or in greenhouse germination tests [28]. Seedling survival after six months post-germination did not show an association to seed size either [29].…”
Section: Ceiba Aesculifoliamentioning
confidence: 99%
“…The storage of nutrients in the cotyledons has a direct influence on the initial growth of the seedlings (Soriano et al, 2011;Bewley et al, 2013;Soriano et al, 2013) and in the dry tropical forest It has been observed that the species that produce larger seeds produce larger seedlings (Soriano et al, 2011), survival in the field (Khurana and Singh, 2004) and in general, an increase in the content of aerial and root biomass (Velázquez-Rosas et al, 2017).…”
Section: Weight Of 100 Seedsmentioning
confidence: 99%